Die »chinesische Avantgarde« und das Dispositiv der Ausstellung: Konstruktionen chinesischer Gegenwartskunst im Spannungsfeld der Globalisierung - Koch, Franziska (transcript, 2016)
Since the 1990s, the reception of contemporary Chinese art in the exhibition format has risen sharply. Exhibitions coined the label »Chinese avant-garde« and enabled a new global dimension of interaction with art production in China. From a transcultural perspective, Franziska Koch answers the question of the constitution of this art with a view to the medial dispositive of the exhibition, in which both China's art images as well as related pictures from China are on display. She critically and diachronically examines the relationship of 20 major exhibitions in the West to development in China and synchronizes the canonizing agents, institutions, and discourses involved.